Modern Technologies of Controlled Release of Biologically Active Substances in Pharmaceutical Research and Development (Review) - E. I. Savelieva (Разработка и регистрация лекарственных средств, 2020)
Introduction. The review describes various systems used as inclusion matrices or modifiers of biologically active substances to enhance their absorption or deposition and subsequent release, both continuous or «on demand», i.e. in response to a stimulus.Text. Technologies for the incorporation of active substances into cyclodextrin nanoaggregates are developed to the greatest extent. Such technologies were used to obtain modified forms of hydrocortisone, glibenclamide, and a number of peptide drugs. Acetylcysteine immobilized on ethyl cellulose or other polymer particles significantly increases the bioavailability of peptide drugs on their intranasal administration. The deposition of active substances in the body takes place by way of their delayed controlled dissolution, adsorption, encapsulation, or esterification. The release of deposited substances upon exposure to an endogenous (change in pH, temperature) or external (exposure to ultrasound, electric or magnetic field, chemical activators) stimulus can be single or multiple, depending on the ability of the accommodating matrix for self-aggregation.Conclusion. Self-aggregated peptides are most promising for stimulus-induced release/delivery of biologically active substances. Modern technologies for the modification of active substances increase the efficiency of their administration and favor targeted location and implementation time of biological effects.